Treatment with the anti-IL-6 receptor antibody attenuates muscular dystrophy via promoting skeletal muscle regeneration in dystrophin-/utrophin-deficient mice - Wada, Eiji; Tanihata, Jun; Iwamura, Akira; Takeda, Shin’ichi; Hayashi, Yukiko K.; Matsuda, Ryoichi (Skeletal muscle, 2017)
Chronic increases in the levels of the inflammatory cytokine interleukin-6 (IL-6) in serum and skeletal muscle are thought to contribute to the progression of muscular dystrophy. Dystrophin/utrophin double-knockout (dKO) mice develop a more severe and progressive muscular dystrophy than the mdx mice, the most common murine model of Duchenne muscular dystrophy (DMD). In particular, dKO mice have smaller body sizes and muscle diameters, and develop progressive kyphosis and fibrosis in skeletal and cardiac muscles. As mdx mice and DMD patients, we found that IL-6 levels in the skeletal muscle were significantly increased in dKO mice. Thus, in this study, we aimed to analyze the effects of IL-6 receptor (IL-6R) blockade on the muscle pathology of dKO mice. Male dKO mice were administered an initial injection (200 mg/kg intraperitoneally (i.p.)) of either the anti-IL-6R antibody MR16-1 or an isotype-matched control rat IgG at the age of 14 days, and were then given weekly injections (25 mg/kg i.p.) until 90 days of age. Treatment of dKO mice with the MR16-1 antibody successfully inhibited the IL-6 pathway in the skeletal muscle and resulted in a significant reduction in the expression levels of phosphorylated signal transducer and activator of transcription 3 in the skeletal muscle. Pathologically, a significant increase in the area of embryonic myosin heavy chain-positive myofibers and muscle diameter, and reduced fibrosis in the quadriceps muscle were observed. These results demonstrated the therapeutic effects of IL-6R blockade on promoting muscle regeneration. Consistently, serum creatine kinase levels were decreased. Despite these improvements observed in the limb muscles, degeneration of the diaphragm and cardiac muscles was not ameliorated by the treatment of mice with the MR16-1 antibody. As no adverse effects of treatment with the MR16-1 antibody were observed, our results indicate that the anti-IL-6R antibody is a potential therapy for muscular dystrophy particularly for promoting skeletal muscle regeneration.